Non-timber forest products in Latin America: an overview - Ruíz Pérez, M. (1997)
Non-timber forest products are today being viewed as legitimate sources of livelihood for local communities. By forming associations, extractivist have achieved some success in having their rights to exploit forested areas recognised and enshrined in legislation and/or receiving increased prices paid for produtcs. The development of legal system of non-timber forest product use has not been without problems. Communities should be involved in decision-making on the management of the forest resource